"Національні історіографії" в умовах соціально-економічних трансформацій і політичних реформ. (Zaporizhzhia Historical Review, 2021)
In clause the author investigates some aspects of formation of a national historical science in Russia and Ukraine, emphasizes their problems, pays attention to interdependence and differences of terms: «the national historiography», «national history», «nationalization of history».